UTILIZATION OF BY-PRODUCTS OF KUNIRAN FISH SURIMI PROCESSING (Upeneus moluccensis) IN THE MAKING OF FISH BALLS - Widya Pangestika; Deden Yusman Maulid; Mochammad Rizky Arfipratama (Aurelia Journal, 2023)
Making Fish balls with the addition of flour as a by-product of processing kuniran fish surimi (Upeneus moluccensis). Fish balls with the addition of flour as a by-product of surimi processing aims to make a diversification of processed fish-based products economically. The use of flour as a by-product of surimi processing as an additional ingredient in making fish balls can increase the nutritional value of fish ball products. Parameters observed were hedonic test (color, aroma, texture, taste and overall) as well as physiochemical analysis which included protein content, water content, and gel strength. In the addition of 10% surimi flour, the treatment of fish balls was the most preferred by the panelists with a color score of 3.8 (likes), aroma 3.5 (likes), texture 3.8 (likes), taste 4.1 (likes), and overall 3.9 (likes). In addition, the results of physiochemical tests, obtained test results data that have differences in each formulation. The results of the water content test for fish balls P1 were 68.90%, fish balls P2 were 64.84%, and fish balls were P3 60.80%. For the test results, the protein content of fish balls P1 was 8.89%, fish balls P2 was 12.66, and fish balls were P3 14.48. Fish balls with the addition of flour as a by-product of processing kuniran fish surimi have met the fish balls standard SNI 01-7266-2014.